Perioperative Anxiety Associated With Mohs Micrographic Surgery: A Survey-Based Study. Issue 7 (18th July 2022) - Long, Jun; Rajabi-Estarabadi, Ali; Levin, Adam; Nami, Navid; Nouri, Keyvan
Abstract : Supplemental Digital Content is Available in the Text. Abstract : BACKGROUND: Mohs micrographic surgery (MMS)-associated anxiety is an important issue that remains poorly discussed. Identifying risk factors for MMS-associated anxiety will better equip physicians to manage patients' preoperative anxiety and result in improved patient satisfaction and outcomes. OBJECTIVE: This study aims in identification of risk factors that may play a role in MMS-associated anxiety among patients with nonmelanoma skin cancer. METHODS: A cross-sectional case series was conducted among MMS patients collect information on patient demographics and surgical locations and to measure perioperative anxiety and quality of life (QoL). In addition, adjusted linear and logistic regression analyses were performed to identify potential risk factors that predict MMS-associated anxiety. RESULTS: Significant increases in perioperative anxiety were associated with the eyelid area compared with the noneyelid facial area and nonfacial area ( p ≤ .05). Patients with graduate degrees exhibited less anxiety compared with ones who received less education ( p ≤ .05). Higher perioperative anxiety was associated with a greater impact on QoL ( p ≤ .05). CONCLUSION: This study identified that surgical location and the patient's educational level are 2 critical predicting factors for perioperative anxiety. Furthermore, perioperative anxiety could negatively affect a patient's quality of life and warrants further investigation into effective management.